Quark sea asymmetry of the nucleon - Mirez, Carlos [UNESP]; Tomio, Lauro [UNESP]; Trevisan, L. A.; Frederico, T. (Elsevier B.V., 2010)
The light anti-quark and quark distribution in the proton, as well as the neutron to proton ratio of the structure functions, extracted from experimental data, are well fitted by a, statistical model of linear-confined quarks. The parameters of the model are given by a temperature, which is adjusted by the Gottfried sum-rule violation, and two chemical potentials given by the corresponding up (u) and down (d) quark normalizations in the nucleon. The quark energy levels are generated by a relativistic linear-confined scalar plus vector potential.